Relationship between family types and moral judgment level in university students - Delgado V., Ana (2010)
Objectives: a. To know the relationship between family types and the moral judgement level of tenth semester Clinical Psychology college students at UNMSM. b. Identify the family types of tenth semester Clinical Psychology college students at UNMSM. c. Identify the moral judgement level of tenth semester Clinical Psychology college students at UNMSM. d. To determine the relationship between the family type and the pr.conventional moral judgement level of tenth semester Clinical Psychology college students at UNMSM. e. To determine the relationship between the family type and the conventional moral judgement level of tenth semester Clinical Psychology college students at UNMSM. Design: Correlational study. Materials and methods: The participants were 55 tenth semester Clinical Psychology college students at UNMSM. It was used the Family Adaptability and Cohesion Evaluation Scales (FACES III) and Gibbs and Widam’s Sociomoral Reflection Objective Measure (SROM). Results: 51 percent of college students are at the conventional moral judgement level. The chaoti.dipersed family type is the most frequent (12) and represents the 22% of the sample. Considering the family operating level, the "middle range" is the most frequent and represents the 51% of participants. Conclusions: The family operating level most frequent is the "middle range" type. Also, the predominant moral judgement is the conventional one. It was found a significative statistical relationship among, family operating "middle range" level and conventional moral judgement level.